Germination and Early Growth of Brassica juncea in Copper Mine Tailings Amended with Technosol and Compost. (23rd January 2014) - Novo, Luís A. B.; González, Luís
Abstract : Mine tailings represent a serious threat to the environment and human health; thus their restoration has become a major concern. In this study, the interactions between Brassica juncea and different mine soil treatments were evaluated in order to understand their effect on germination and early growth. Three soil treatments containing 25% and 50% of technosol and 30% of compost were prepared. Germination and early growth were assessed in soil and pore water extracts from the treatments. Unlike the untreated mine soil, the three treatments allowed germination and growth, achieving levels comparable to those of seedlings from the same species developed in normal conditions. The seedlings grown in 50% of technosol and 30% of compost exhibited greater germination percentages, higher growth, and more efficient mechanisms against oxidative stress, ascribed to the organic matter and nutrients content of these treatments. Considering the unequivocal ability of B. juncea for phytoremediation, the results suggest that technosol and compost may be an auspicious solution to allow the germination and early growth of this species in mine tailings.